2014
DOI: 10.1371/journal.pone.0101890
|View full text |Cite
|
Sign up to set email alerts
|

Rates of Litter Decomposition and Soil Respiration in Relation to Soil Temperature and Water in Different-Aged Pinus massoniana Forests in the Three Gorges Reservoir Area, China

Abstract: To better understand the soil carbon dynamics and cycling in terrestrial ecosystems in response to environmental changes, we studied soil respiration, litter decomposition, and their relations to soil temperature and soil water content for 18-months (Aug. 2010–Jan. 2012) in three different-aged Pinus massoniana forests in the Three Gorges Reservoir Area, China. Across the experimental period, the mean total soil respiration and litter respiration were 1.94 and 0.81, 2.00 and 0.60, 2.19 and 0.71 µmol CO2 m−2 s−… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(39 citation statements)
references
References 65 publications
0
39
0
Order By: Relevance
“…Most carabids are active on the ground, some species lay eggs in burrows, and others overwinter as larvae or as adults in the soil. For these reasons, soil properties, such as softness, water content, temperature, etc., influence the carabid community [21,[59][60][61][62]. Microclimatic conditions affect carabid assemblages, particularly through different species affinities for moisture, sunlight, and warmth.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most carabids are active on the ground, some species lay eggs in burrows, and others overwinter as larvae or as adults in the soil. For these reasons, soil properties, such as softness, water content, temperature, etc., influence the carabid community [21,[59][60][61][62]. Microclimatic conditions affect carabid assemblages, particularly through different species affinities for moisture, sunlight, and warmth.…”
Section: Discussionmentioning
confidence: 99%
“…As regards the influence of soil factors on diversity and dominance, we found that soil litter positively influenced diversity and evenness, and negatively influenced dominance, in the desert steppe. Carabids are known to be influenced by the amount of soil litter, because it modulates both soil moisture and temperature, and improves fertility, food availability, and habitat heterogeneity [21][22][23]61]. These important functions are further enhanced in desert ecosystems, where vegetable detritus represents a prominent trophic source.…”
Section: Discussionmentioning
confidence: 99%
“…First, SOC content in tidal field before afforestation (for example, only 5.30 g kg -1 ) is far lower than that in agricultural land and abandoned land in the same area (11.10, 14.47 g kg -1 , respectively) [3]. Second, the study site was located in the edge of north subtropical monsoon climate area, which had high litter decomposition rate and soil respiration rate due to the high temperature and humidity, accelerating decomposition speed of organic substance and reducing the content of SOC in soil [44]. While, the SOC stocks approaches the average of natural forests in China after 33 years of afforestation for M. glyptostroboides, which shows a significant C sequestration for afforestation in coastal China.…”
Section: Discussionmentioning
confidence: 89%
“…Litter contributions to soil respiration exceeding 50 % have been reported in the literature (e.g. Xiao et al, 2014).…”
Section: Model Selection and Imputationmentioning
confidence: 99%